Preparation and characterization of interpenetrating networks based on polyacrylates and poly(lactic acid) - H. Kaczmarek; I. Vukovic-Kwiatkowska (eXPRESS Polymer Letters)
Three different, multifunctional acrylic monomers were photopolymerized in a matrix of poly(lactic acid), PLA, using 2-hydroxy-2-methyl-1-phenyl-propan-1-one as a photoinitiator. The kinetics of the photopolymerization of monomers in PLA, studied with Fourier Transform Infrared Spectroscopy, has been compared to analogous processes of pure monomers under the same conditions (room temperature, air atmosphere). Additionally, poly(ethylene glycol) was added to acrylate/PLA blends as plasticizer.The highly crosslinked networks obtained were characterized by FTIR and optical microscopy. The amount of insoluble gel has been estimated gravimetrically. It was found that the studied systems are characterized by very high polymerization rate, moreover, efficient grafting of polyacrylates on PLA takes place. The observed morphology indicates the heterogeneity of formed networks. The glass transition temperature of PLA in studied blends has been determined by differential scanning calorimetry.